2018
DOI: 10.1111/jgs.15260
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Hospice Care at Home Versus in an Assisted Living Facility or Nursing Home

Abstract: There were significant differences in characteristics of individuals whose family members did and did not return surveys, which has implications for use of after-death surveys to evaluate hospice quality. Lower perceived quality of hospice care in NHs may be related to general dissatisfaction with receiving care in this setting. Survey results have the potential to set priorities for quality improvement, choice of provider, and potentially reimbursement. Underlying causes of differences of perceived quality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Some of the employees in the institution are young nurses, and this is their first working experience of palliative care. They are all enthusiastic and having dreams of changing the world, and working here makes them feel proud [17]. In addition, several of the senior employees, who had been helped by others before, were grateful and hoped to give back to society.…”
Section: Discussionmentioning
confidence: 95%
“…Some of the employees in the institution are young nurses, and this is their first working experience of palliative care. They are all enthusiastic and having dreams of changing the world, and working here makes them feel proud [17]. In addition, several of the senior employees, who had been helped by others before, were grateful and hoped to give back to society.…”
Section: Discussionmentioning
confidence: 95%
“…Of note, despite evidence that older adults may prefer to avoid nursing home admission close to death, 19 presence in assisted living on the day of death is not a guarantee of high-quality end-of-life care. There is also general agreement about the difficulty of predicting end-of-life disease trajectories among frail older adults, and especially the individuals with dementia, making the management of care transitions to and from assisted living particularly challenging near the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a contributing factor that we were unable to study in our analysis was the setting (e.g., home, hospital, hospice inpatient) in which patients received hospice care. Prior studies have reported better quality of hospice care when it is delivered at home vs in nursing homes (NH) and assisted living facilities (ALF) 16,17 and a greater proportion of dementia patients on hospice receive care in an NH and ALF when compared with other terminal diagnoses. 17 This calls for further research looking into the care that is received in different hospice settings and how that may impact the differences we see in care for dementia patients at the end-of-life.…”
Section: Discussionmentioning
confidence: 99%